Ten lectures on a diachronic constructionalist approach to discourse structuring markers - Traugott, Elizabeth Closs 1939- (Brill, 2022)
"To date little work has been done on pragmatics within cognitive linguistics, especially from a historical perspective. The lectures presented in this volume give the first systematic account of how pragmatics can be incorporated into cognitive linguistics using a Diachronic Construction Grammar perspective. The author combines detailed study of the historical development of Discourse Structuring Markers like all the same, after all and by the way and propose ways in which to model them. A number of topics are addressed including what a usage based approach to language change is, differences between innovation and change, how to think about analogy and networks, how combinations of Discourse Structuring Markers like now then became a unit, and whether clause-initial and -final positions are constructions. Refinements of Diachronic Construction Grammar are proposed and tested"--
Keywords: Pragmatik; Konstruktionsgrammatik; Diskursmarker; Construction grammar / Congresses; Discourse markers / Congresses; Pragmatics / Congresses; Cognitive grammar / Congresses; Cognitive grammar; Construction grammar; Discourse markers; Pragmatics; Conference papers and proceedings; Lectures; Konferenzschrift